Effect of long-term exercise on circulating ghrelin in overweight and obese individuals: a systematic review and meta-analysis - Xin, Xianyang; Wang, Hai; Guo, Yongqing; Xie, Jun (Frontiers in Nutrition, 2025)
ObjectiveGhrelin, also known as the “hunger hormone,” is a pivotal hormone in controlling appetite, and it is the only known gastrointestinal hormone that promotes food intake, contributing to the regulation of energy balance and body weight. However, studies on the long-term effects of exercise on ghrelin levels in obese populations have shown conflicting results. This study aims to summarize RCT experiments exploring changes in ghrelin levels following long-term exercise in obese or overweight individuals through meta-analysis.MethodsThis study employed meta-analytical techniques, searching databases such as PubMed, Web of Science, and EMBASE, to gather research on exercise and ghrelin. The quality of the studies was assessed according to the Cochrane Handbook standards, and data analysis for ghrelin, BMI, and weight was performed using RevMan 5.4 and Stata 16.0 software. A total of 13 interventions involving 944 participants were included to systematically investigate the regulatory effects of exercise on ghrelin levels in obese and overweight individuals. Meta-analytical results were calculated using standardized mean differences (SMDs).ResultsExercise interventions significantly increased ghrelin levels (SMD =1.16, 95% CI = 0.52 to 1.80, p < 0.0001), with high inter-study heterogeneity (I2 = 90%). Subgroup analysis suggested that RT and AE + RT were more effective than AE. For BMI, exercise led to a significant reduction (SMD = −0.43, 95% CI = −0.69 to −0.16, p = 0.002), with low heterogeneity (I2 = 21%). Similarly, exercise significantly reduced weight (SMD = −0.54, 95% CI = −0.98 to −0.11, p = 0.01), though with high heterogeneity (I2 = 75%). These results suggest exercise effectively improves ghrelin levels, BMI, and weight.ConclusionProlonged exercise interventions demonstrated a statistically significant effect on ghrelin levels. This indicates that exercise interventions can elevate ghrelin levels, which may be associated with reductions in BMI and weight.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42024588259.